Contesting Transgender Identity in Contemporary Indonesia: Religious Discourses through the Lens of Young Muslim Scholars - Qoimah, Roviatul; Alifatul Lusiana Uswatun Chasanah (Faculty of Ushuluddin and Philosophy, 2024)
This study investigates the growing visibility of transgender individuals in contemporary Indonesia and the complex moral, social, and religious tensions it provokes, particularly among Muslim scholars (ulama). As transgender identities gain increasing representation—especially through media and entertainment—they challenge prevailing religious norms and raise questions about the boundaries of moral authority in Islam. This research asks how influential figures such as Abdul Somad, Buya Yahya, and Gus Baha’ frame and interpret transgender existence within their theological discourses, and what these interpretations reveal about the broader Islamic moral response to gender nonconformity. To deepen the analysis, the study also draws on Søren Kierkegaard’s existentialist framework—specifically his concepts of the aesthetic, ethical, and religious stages of life—as a philosophical lens through which the inner struggle of transgender identity can be understood. Using qualitative library research, this paper finds that Indonesian ulama predominantly construct transgender identity as a deviation from Islamic principles, while Kierkegaard’s existential stages offer an alternative understanding that situates transgender experience as a tension between self-expression and spiritual surrender.